Impact of Argo Observation on the Regional Ocean Reanalysis of China Coastal Waters and Adjacent Seas: A Twin-Experiment Study - Caixia Shao; Lili Xuan; Yingzhi Cao; Xiaojian Cui; Siyu Gao (Advances in Meteorology)
A regional ocean reanalysis system of China coastal waters and adjacent seas, called CORA (China ocean reanalysis), has been recently developed at the National Marine Data and Information Service (NMDIS). In this study, based on CORA, the impact of Argo profiles on the regional reanalysis is evaluated using a twin-experiment approach. It is found that, by assimilating Argo observations, the reanalysis quality is much improved: the root mean square (RMS) error of temperature and salinity can be further reduced by about 10% and the RMS error of current can be further reduced by 18%, compared to the case only assimilating conventional in situ temperature and salinity observations. Consistent with the unique feature of Argo observations, the temperature is improved in all levels and the largest improvement of salinity happens in the deep ocean. Argo profile data have a significant impact on the regional ocean reanalysis through improvements of both hydrographic and dynamic fields.